2019
DOI: 10.1111/nan.12528
|View full text |Cite
|
Sign up to set email alerts
|

Histological heterogeneity in a large clinical cohort of juvenile idiopathic inflammatory myopathy: analysis by myositis autoantibody and pathological features

Abstract: Aim Juvenile idiopathic inflammatory myopathies have been recently reclassified into clinico‐serological subgroups. Myopathological correlates of the subgroups are incompletely understood. Methods We studied muscle biopsies from 101 children with clinically and serologically defined juvenile idiopathic inflammatory myopathies from the UK JDM Cohort and Biomarker Study by applying the international JDM score tool, myopathological review and C5b‐9 complement analysis. Results Autoantibody data were available for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 26 publications
1
27
0
1
Order By: Relevance
“…In a recent study which included a detailed evaluation of 101 JDM biopsies the UK group has shown that severity of biopsy features is significantly different in different MSA groups with Mi2 positive cases having classic, severe features, MDA-5 positive cases having mild or minimal pathological changes. However, both the anti-TIF1-γ and anti-NXP2 positive groups were heterogeneous in terms of severity and features on biopsy [114] . Interestingly the degree of IFN driven expression of MxA protein in muscle biopsies was also found to be differentially expressed in different MSA groups as well as correlating with weakness as measured by the CMAS clinical score [115] .…”
Section: Juvenile Manifestations Of Dm and Inherited Interferonopathiesmentioning
confidence: 94%
“…In a recent study which included a detailed evaluation of 101 JDM biopsies the UK group has shown that severity of biopsy features is significantly different in different MSA groups with Mi2 positive cases having classic, severe features, MDA-5 positive cases having mild or minimal pathological changes. However, both the anti-TIF1-γ and anti-NXP2 positive groups were heterogeneous in terms of severity and features on biopsy [114] . Interestingly the degree of IFN driven expression of MxA protein in muscle biopsies was also found to be differentially expressed in different MSA groups as well as correlating with weakness as measured by the CMAS clinical score [115] .…”
Section: Juvenile Manifestations Of Dm and Inherited Interferonopathiesmentioning
confidence: 94%
“…The importance of TLR4 in DM is highlighted by the presence of TLR4+ cells in the perimysium of these patients [13]. Also, patients with anti-Mi2 antibodies are characterized by intense myositis and an abundant inflammatory infiltrate in muscle biopsy [52]. In this regard, TLR4 is a key mediator of the pathogenic autoimmune and inflammatory response in IIM.…”
Section: Discussionmentioning
confidence: 99%
“…Both studies reported anti-MDA5 antibody to be strongly associated with ILD; however, only 8 (18%) of the 44 Japanese cases and none of the UK patients developed RP-ILD. A recent cohort study in the UK observed low myositis severity scores depending on muscle biopsies in 11 anti-MDA5 antibody-positive patients 15 .…”
Section: Epidemiology and Characteristic Clinical Features Of Subgroumentioning
confidence: 98%